Rendimiento intelectual de niños-infantes a adolescentes de clase socio-económica media y baja de Lima y de algunas provincias - Majluf, Alegría (1984)
The author reviews a certain number of studies (many of them unpublished) that compare intelectual performance of children as well as adolescents from different social classes in Peru. The results sistematically point to a serious deficit in the case of lower-class children, speciaiJy from rural areas. Also are analyzed interactions between economic, age and gender variables. A proposal is made for the carefully research of the intelectual profile of peruvian children according to the region where they live in.